Exploring the Impact of Local Traditional Systems on the Modernization of Civic Life in Dhaka (1864-1947): Context Panchayet System - Hossain, Mohammad Jahangir (Jagannath University Journal of Arts, 2026)
The article 'Exploring the Impact of Local Traditional Systems on the Modernization of Civic Life in Dhaka ( 1864-1947): Context Panchayet System' analyzes the role of organic and traditional institutions in the production of urban modernity in Dhaka. It examines how indigenous systems shaped the transformation of citizen life during the city’s transition under colonial rule. The Panchayat system is employed as a critical example of a traditional institution that mediated social order and civic practices. While modernity is a contested and plural concept, colonial interventions significantly reconfigured Dhaka from a Mughal urban center into a British colonial town. However, this transformation did not follow a linear or uniform trajectory. Instead, traditional institutions continued to operate alongside colonial forms of governance. Urban historians conceptualize this process as "indigenous modernity", emphasizing the active role of local practices in shaping modern urban life. This article explores how the Panchayat system functioned within the colonial modernizing framework and contributed to the making of modern citizenship. It further examines the dynamics of duality, contestation, and negotiation between traditional authority and colonial modernity in shaping the everyday livelihoods of Dhaka’s citizens. Jagannath University Journal of Arts, v-15, i-2, 2025:p1-13